2018
DOI: 10.1080/00981389.2018.1430091
|View full text |Cite
|
Sign up to set email alerts
|

Bio-psycho-social-spiritual needs of adolescents and young adults with life-threatening illnesses: Implications for social work practice

Abstract: This paper explores the biopsychosocial and spiritual needs of adolescents and young adults (AYA) with life-threatening or terminal illnesses. AYA are situated between childhood and adulthood (ages 15-25) and have distinct biopsychosocial and spiritual needs unique to their developmental stage. Having a life-threatening or terminal illness directly challenges normal AYA developmental tasks and identity formation. AYA experience more troubling physical symptoms during the dying process compared to other age gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 53 publications
0
26
0
1
Order By: Relevance
“…A better way of approaching, understanding and supporting young adults may be to consider where they are in their life course, as there may be more in common, than different, between those with similar life course experiences, for example, being in education, maintaining a career, having children or caring responsibilities. The usefulness of taking such an approach is also found in the wider literature on end-of-life care for young adults and so reinforces this finding 20. Adolescence and young adulthood is a developmental stage when individuals shape their identities, gain autonomy, make career choices and develop intimate relationships.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…A better way of approaching, understanding and supporting young adults may be to consider where they are in their life course, as there may be more in common, than different, between those with similar life course experiences, for example, being in education, maintaining a career, having children or caring responsibilities. The usefulness of taking such an approach is also found in the wider literature on end-of-life care for young adults and so reinforces this finding 20. Adolescence and young adulthood is a developmental stage when individuals shape their identities, gain autonomy, make career choices and develop intimate relationships.…”
Section: Discussionmentioning
confidence: 59%
“…Adolescence and young adulthood is a developmental stage when individuals shape their identities, gain autonomy, make career choices and develop intimate relationships. A cancer diagnosis at this stage is ‘off-time’ during the normative life cycle: life is interrupted, developmental tasks and identity formation are challenged and few peers will share their cancer experience 20. In common with Soanes and Gibson, we found that participants across this age range reported a desire to maintain these aspects of their life, as well as their identity, for example, as a student, a professional or parent, in part to maintain a sense of normality and control 21…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under this framework, the genetic, cellular, and physiological underpinnings of CF are examined, all of which are collectively treated as the main indicators of one's quality of life (Borowitz et al, 2016;Chandler et al, 2018;Marshall & Nelson, 2014). Only recently has the literature on health research witnessed a shift toward embracing the biopsychosocial model, which also highlights one's psychological and social functioning in response to illness (Beerbower, Winters & Kondrat, 2018;Brown, 2007;Failo et al, 2018). A meta-analysis conducted by Pinquart examined body image issues among youth with CF as well as diseases such as scoliosis, cancer, and diabetes (2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In terms of using creative expression to explore the psychosocial dimensions of CF, most studies have employed art forms such as poetry, visual arts, and music (Daveson & Kennelly, 2000;Fenton, 2000;MacDonald, 2017). Of these studies, most use artistic expression as a practical means to evaluate the communication of psychosocial experiences (Beerbower et al, 2018;MacDonald, 2017;Pop-Jordanova et al, 2016). Such studies are significant as they advocate the notion that art is a valid data collection and dissemination tool to provide nuanced insight into the lived experiences of those with CF (Beerbower et al, 2018;MacDonald, 2017;Pop-Jordanova et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%